PENGEMBANGAN MEDIA PEMBELAJARAN FLASH CARD BERBAHAN LIMBAH SERABUT KELAPA PADA MATERI OPERASI HITUNG BILANGAN BULAT DI KELAS IV SDN 064037 MEDAN TEMBUNG: Penelitian Pengembangan - Putri Andini; Elvi Mailani; Fahrur Rozi; Albert Pauli Sirait; Lidia Simanihuruk (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to produce valid, practical and effective flash card learning media made from coconut fiber waste on integer arithmetic operation material on multiplication and division of tens and hundreds in grade IV-B of SDN 064037 Medan Tembung. This study is a Research and Development (R&D) using a 4D development model consisting of Define, Design, Development and Disseminate. The subjects of this study were 20 students of grade IV-B of SDN 064037 Medan Tembung. The data analysis technique in this study was qualitative data obtained from interviews, responses and suggestions from media validators, materials, and education practitioners (teachers). While quantitative data were obtained from questionnaires given to media experts, material experts, education practitioners and student response questionnaires. The results of the study showed that the validity assessment by media experts (lecturers) obtained a percentage of 92% with the criteria "Suitable for Use with Revision", validity by material experts (lecturers) obtained a percentage of 95% with the criteria "Very Suitable". Furthermore, the practicality assessment by grade IV teachers obtained a percentage of 98% with the criteria "Very Practical" and the student response questionnaire obtained a percentage of 98% with the criteria "Very Good". The results of the assessment with the pretest results obtained 59.25% with the criteria "Quite Good" and the posttest results obtained 81.5% with the criteria "Very Good". Based on the effectiveness of the use of flash card learning media made from coconut fiber waste using N-Gain obtained the criteria "Quite Effective" with a percentage of 58.75%. It can be concluded that this research and development produces a product in the form of a flash card learning media made from coconut fiber waste that is valid, practical and effective to be used in the learning process in class IV SDN 064037 Medan Tembung.